Neomyogenesis in 3D Dynamic Responsive Prosthesis for Inguinal Hernia Repair. Issue 12 (14th October 2018) - Amato, Giuseppe; Romano, Giorgio; Puleio, Roberto; Agrusa, Antonino; Goetze, Thorsten; Gulotta, Eliana; Gordini, Luca; Erdas, Enrico; Calò, Piergiorgio
Abstract: Despite undisputed improvements, prosthetics hernia repair continues to be affected by unacceptable rates of complications. Postoperative adverse events such as discomfort and chronic pain represent a subject of increasing concern among the surgical community. Poor quality biologic response, stiff scar plates, and mesh shrinkage, a typical effect of conventional static meshes and plugs, are all indicated as the main reasons for many of the complications related to inguinal hernia repair. Even the conventional concept of treatment based upon a supposed reinforcement of the groin consequent to the fibrotic incorporation of meshes, would appear to be inadequate in the light of the latest scientific evidence concerning the degenerative genesis of inguinal hernia. Following these recent studies, a newly conceived 3D dynamically responsive implant has been developed. It concerns a multilamellar shaped prosthesis, intended to be placed fixation‐free to obliterate the hernia defect. This 3D structure has already demonstrated to induce a probiotic biological response with development of viable tissue, instead of the fibrotic plaque typical of conventional meshes. Newly formed elastic fibers, neo‐angiogenesis, and neo‐nerve genesis in a surrounding of well perfused connective tissue are the typical elements of the biologic response in the newly conceived implant. In addition to these elements, muscle fibers have also been detected in the implant structure. The aim of this research was to determine the ingrowth of muscle fibers in the implant by assessing the quantity and quality of muscle development in the short, medium, and long term post‐implantation. Histological examination of biopsy samples excised from patients who underwent dynamic hernia repair with the 3D dynamic implant showed the presence of muscular elements that in the short term could be described as multiple spots of myocytes in the early stage of development. Over the mid‐ to long‐term, muscle fibers increased in number and level of maturation, assuming the typical aspect of standard muscle bundles in the final phase. Effectively, long term, myocytes histologically evidenced the distinctive arrangement of the muscle structure, with nuclei and striated elements being similar to normal muscle elements. The development of this highly specialized connective tissue in the 3D dynamic responsive implant seems to document the finalization of an enhanced biologic response leading to the ingrowth of typical tissue components of the groin. Reverting degenerative pathogenesis into effective regeneration recognized in the newly conceived 3D prosthesis would appear to represent a significant concept change in the repair of inguinal hernias.